2021
DOI: 10.1002/aelm.202100804
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Two‐Channel Magnetotransport in SrRuO3 Ultrathin Films Achieved by Controlling the Kinetics of Heterostructure Deposition

Abstract: In the field of oxide heterostructure engineering, there are extensive efforts to couple the various functionalities of each material. The Berry curvature‐driven magnetotransport of SrRuO3 ultrathin films is currently receiving a great deal of attention because it is extremely sensitive to the electronic structures near the Fermi surface driven by extensive physical parameters such as spin–orbit coupling and inversion symmetry breaking. Although this is beneficial in terms of heterostructure engineering, it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Notably, a decrease in H c,2 coincides with an increase in RRR (Figure 1e), implying that the easier switching of the magnetization of this domain may be associated with a higher RRR. Since magnetization is sensitive to the structure, our hypothesis that there may be subtle structural changes in the films within the growth window from the distribution of pinning centers for magnetization switching (such as inhomogeneities at the nanoscale) due to the different growth conditions and kinetics 12,42 that are not captured by laboratory-based X-ray diffraction appears plausible.…”
Section: Adsorption-controlled Growth Window In Solidmentioning
confidence: 99%
“…Notably, a decrease in H c,2 coincides with an increase in RRR (Figure 1e), implying that the easier switching of the magnetization of this domain may be associated with a higher RRR. Since magnetization is sensitive to the structure, our hypothesis that there may be subtle structural changes in the films within the growth window from the distribution of pinning centers for magnetization switching (such as inhomogeneities at the nanoscale) due to the different growth conditions and kinetics 12,42 that are not captured by laboratory-based X-ray diffraction appears plausible.…”
Section: Adsorption-controlled Growth Window In Solidmentioning
confidence: 99%
“…Moreover, van Thiel et al reported that charge discontinuity in the SRO/LaAlO 3 interface can result in the broken inversion symmetry, thus inducing both magnetic and topological reconstruction in the SRO layer. Nonetheless, the hump-like Hall signal may also result from SRO inhomogeneity and can be explained by a two-channel anomalous Hall effect (AHE) model. Ren et al reported that the observed nonmonotonic anomalous Hall resistivity behavior in the BFO/SRO bilayer system can be attributed to SRO inhomogeneity instead of THE. Ko et al found that the stoichiometry and lattice deformation of the SRO layer can be manipulated by controlling the growth pressure of the LaAlO 3 capping layer, thus resulting in two-channel AHE signals.…”
Section: Introductionmentioning
confidence: 99%
“…23−26 Ren et al 25 observed nonmonotonic anomalous Hall resistivity behavior in the BFO/SRO bilayer system can be attributed to SRO inhomogeneity instead of THE. Ko et al 26 found that the stoichiometry and lattice deformation of the SRO layer can be manipulated by controlling the growth pressure of the LaAlO 3 capping layer, thus resulting in two-channel AHE signals.…”
Section: Introductionmentioning
confidence: 99%